Challenges and Realities of Social Participation in Basic Education: A Systematic Literature Review - Bravo-Delgado, Monserrat (2020)
The international educational policy considers social participation as a benchmark for the analysis and the addition of efforts at the local level. Its implementation makes it possible to build schools with greater autonomy and connection with the needs of the social, cultural, and economic context. This work aims to systematically analyze recent studies conducted in Ibero-America in relation to social or community participation to know the proposals implemented to promote it, its structure as educational policy, its main challenges, and what practices favor or hinder it. Through a systematic search in two databases (SCIELO and Redalyc), 759 articles published between 2013 and 2018 have been located. Through a filtering process, the following were the criteria to select the articles: a) the use of terms: social participation or community participation; b) research related to the educational field; c) studies conducted in institutions of basic level; and d) studies developed in Ibero-America. Eighteen research works were collected and classified according to the following categories: perspectives of social participation, description of experiences, and evaluation of social participation. The main findings point to a tendency to implement social participation as an educational policy, which has not been consolidated, representing a theoretical commitment that is not always concrete in practice. Therefore, it is important to generate research to establish proposals to stimulate the creation of spaces and participatory dynamics.